UVESCREEN1: A randomised feasibility study of imaging-based uveitis screening for children with juvenile idiopathic arthritis- Study Protocol - Sonali Dave; Jugnoo S. Rahi; Harry Petrushkin; Ilaria Testi; Dipesh E. Patel; Ameenat Lola Solebo (PLoS ONE, 2025)
Children with Juvenile Idiopathic Arthritis (JIA) are at a currently unpredictable risk of a blinding, often asymptomatic, co-existent eye disorder, anterior uveitis which requires prompt treatment. The unpredictability of this insidious disorder commits children with JIA to three-monthly expert clinical examinations in specialist eye centres often located far from their homes. Optical coherence tomography of the ocular anterior segment (AS-OCT) has been shown to be an acceptable, repeatable and sensitive modality for uveitis detection, but is not standard care. This feasibility randomised controlled trial (RCT) aims to inform a future full-scale RCT comparing current routine practice (expert slit lamp examination, SLE) to AS-OCT for the surveillance of uveitis in children at risk. Eighty children aged between 2 and 12 years old and diagnosed with JIA within the preceding year will be included. Participants with an existing diagnosis of uveitis, other ocular co-morbidities or those unable to complete examinations or provide informed assent will be excluded. Participants will be randomised to SLE (control) or AS-OCT (intervention) examination at a frequency consistent with the current national programme for childhood uveitis surveillance. Children in the intervention arm will also have standard examination at 6 and 12 months after study entrance. Outcomes of interest will be feasibility (recruitment and attrition rates), clinical metrics (proportion diagnosed with uveitis or other ocular disorders at 12 months after study entrance), quality of life outcomes (PedsQL), and resource use. Additionally, comparative analysis of AS-OCT versus SLE (‘gold standard’ reference testing) findings at 6 and 12 months for those in the intervention arm will provide the proof-of-concept data necessary to develop and undertake a larger scale trial. Trial registration: This trial has been registered with clinicaltrails.gov ( NCT05984758 ).